2002
DOI: 10.1026//0044-3409.210.4.197
|View full text |Cite
|
Sign up to set email alerts
|

Soziale, personale, methodische oder fachliche: Welche Kompetenzen zählen bei der Bewältigung von Optimierungsaufgaben in betrieblichen Gruppen?

Abstract: Zusammenfassung. In der aktuellen Managementliteratur wird z.T. der Eindruck vermittelt, die Sozialkompetenz sei nicht als Ergänzung zu fachlichem Können zu verstehen, sondern könne dieses ersetzen. Aber: Wie steht es tatsächlich um die Bedeutung der Sozialkompetenz und welche Rolle spielen neben sozialen Kompetenzen fachliche, methodische und personale Kompetenzaspekte bei der Bewältigung von Optimierungsaufgaben? Zur Kompetenzmessung werden Verhaltensdaten von 59 Gruppen aus 19 Unternehmen beim Bewältigen vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 5 publications
0
5
0
12
Order By: Relevance
“…Kauffeld, 2006a;Kauffeld et al, 2002). The number of complaining statements, on the other hand, showed medium negative correlations with the above-mentioned measures of success.…”
Section: Terminating Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Kauffeld, 2006a;Kauffeld et al, 2002). The number of complaining statements, on the other hand, showed medium negative correlations with the above-mentioned measures of success.…”
Section: Terminating Discussionmentioning
confidence: 87%
“…As we explain in more detail below, we chose these two forms of communicative behaviours because past research has revealed these two behaviours are present in these optimization discussions (Kauffeld, 2006a;Kauffeld, 2008;Kauffeld, Frieling, & Grote, 2002), and because group participants have linked them to the production of positive (solution-oriented statements) and negative (complaining statements) affective states.…”
Section: Complaints and Affective Statesmentioning
confidence: 98%
“…These new circumstances have led to discussions focusing on integrated approaches to tourism education including contemporary, content-specific disciplines and a list of skills and competencies termed employability, soft skills, personal skills, generic skills, attributes or capabilities (Atkins, 1999; Hager and Holland, 2006; Holmes, 2001). If competencies are classified, the literature distinguishes among several types of and approaches to competencies, which are summarised as follows (Kauffeld et al, 2002; Kolb, 2002; Sonntag and Schmidt-Rathjens, 2004): Professional competencies comprise skills, abilities and knowledge necessary to meet the challenges and tasks of one’s profession; Methodological competencies are universal problem-solving and decision-making competencies that may be applied in one’s job and in one’s personal surroundings; Social competencies are abilities that enable to act in social surroundings and includes cooperating with other people, interacting with them and building effective relationships; and Leadership competencies are abilities that display inspiration for a shared vision to enable others to act or to encourage them. …”
Section: Fundamental Premises and Discussionmentioning
confidence: 99%
“…These new circumstances have led to discussions focusing on integrated approaches to tourism education including contemporary, content-specific disciplines and a list of skills and competencies termed employability, soft skills, personal skills, generic skills, attributes or capabilities (Atkins, 1999;Hager and Holland, 2006;Holmes, 2001). If competencies are classified, the literature distinguishes among several types of and approaches to competencies, which are summarised as follows (Kauffeld et al, 2002;Kolb, 2002;Sonntag and Schmidt-Rathjens, 2004):…”
Section: Systematic Identification and Implementation Of Enablersmentioning
confidence: 99%
“…But social skills on their own do not enable either the generation of new information and solutions (cf. Kauffeld et al, 2002) or the exploitation of existing knowledge. Instead, they only support the exchange of information, serve as the mechanism to understand communication partners and should help to establish necessary social relations that underlie the exploration and exploitation process.…”
Section: Relevance Of Social Competencies In Exploration and Exploitamentioning
confidence: 99%